2018
DOI: 10.18092/ulikidince.363126
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Capital Structure: Empirical Evidence From Traditional Airlines

Abstract: The purpose of this study is to examine the factors that define capital structure of airlines with traditional business model by taking into account the capital structure theories. In line with this purpose, 31 airline companies, which have continuous financial data during the 2004-2015 period, were examined. Panel data analysis was used as a method in the study. Empirical findings of the study show that traditional airlines operate in line with the Trade-off Theory when determining their long-term debt ratio.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 54 publications
(68 reference statements)
0
7
0
Order By: Relevance
“…When the findings of the study are compared with the previous studies in literature (see Kiracı and Aydın, 2018a;Kiracı and Aydın, 2018b), the long-term financing behavior of airlines that are members of global alliances is similar to airlines implementing lowcost business models and traditional business models. Therefore, long-term financing behavior of both airlines that are members of global alliances and airlines that are implementing low-cost and traditional business models are appropriate to the Trade-Off Theory.…”
Section: Discussionmentioning
confidence: 77%
See 4 more Smart Citations
“…When the findings of the study are compared with the previous studies in literature (see Kiracı and Aydın, 2018a;Kiracı and Aydın, 2018b), the long-term financing behavior of airlines that are members of global alliances is similar to airlines implementing lowcost business models and traditional business models. Therefore, long-term financing behavior of both airlines that are members of global alliances and airlines that are implementing low-cost and traditional business models are appropriate to the Trade-Off Theory.…”
Section: Discussionmentioning
confidence: 77%
“…On the other hand, it is observed that the airlines, which have high growth opportunities, non-debt tax shielding and liquidity ratios have a relatively lower liability ratio. When we compare Model 2 findings with other studies in literature (see Kiracı and Aydın, 2018a;Kiracı and Aydın, 2018b), it is seen that the long-term debt behavior of the member airlines of the global alliances is similar to the traditional business model in terms of growth opportunities and firm size. In addition, the longterm debt behavior of the member airlines of the global alliances is similar to that of the traditional business model and low-cost business model in terms of non-debt tax shield and asset structure.…”
Section: Number Of Groups = 26mentioning
confidence: 69%
See 3 more Smart Citations